1999
DOI: 10.1016/s0272-6963(99)00009-1
|View full text |Cite
|
Sign up to set email alerts
|

Operations management research: an update for the 1990s

Abstract: The issue of operations management (OM) research agendas was first advanced in the literature in 1980 with updates and additions in 1981, 1987, and 1989. We believe that the time is ripe for an analysis of the OM research agenda in the decade of the 90's. In this study, we examine operations management research methodologies and output during the period 1992–1997. Amoako‐Gyampah and Meredith [Amoako‐Gyampah, K., Meredith, J.R., 1989. Journal of Operations Management 8, 250‐262] published a study in which they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 6 publications
5
113
1
6
Order By: Relevance
“…Finally, a more restricted 2 search using a combination of sport and OM keywords was conducted in three databases (Proquest, ScienceDirect and ISI Web of Science). The keywords were identified based on OM textbooks, review articles of the OM field (Prasad and Babbar, 2000;Pannirselvam et al 1999), prior experience and reviews of sport related material. Each author individually provided a list of keywords and these were combined to develop the final lists.…”
Section: Methodology: Systematic Literature Review Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a more restricted 2 search using a combination of sport and OM keywords was conducted in three databases (Proquest, ScienceDirect and ISI Web of Science). The keywords were identified based on OM textbooks, review articles of the OM field (Prasad and Babbar, 2000;Pannirselvam et al 1999), prior experience and reviews of sport related material. Each author individually provided a list of keywords and these were combined to develop the final lists.…”
Section: Methodology: Systematic Literature Review Processmentioning
confidence: 99%
“…Table 1 contains information on units of analysis, method, topic area and sampling in each of the reviewed papers. After a review of the selected papers was conducted, the papers were categorized into nine operations management topics derived from Pannirselvam et al (1999) and Prasad and Babbar (2000). Specifically, the following categories are adopted from these studies and are used to structure the findings of the review:…”
Section: Literature Review: Operations Management In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…With an analysis of 1754 articles published in seven Operations Management journals published between 1992 and 1997, Pannirselvam et al (1999) examined the popular topics and research methods in OM research. They identified and classified the studies that address multiple topics in OM research, and presented the frequency of topics in previous research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amoako-Gyampah & Meredith (1989), Pannirselvam et al (1999), Pilkington & Fitzgerald (2006) and Taylor & Taylor (2009) have focused on identifying the topics and corresponding methods in OM studies. Schniederjans et al (2009) suggested that keywords indicate the article content fairly since the articles are evaluated through a review process by journal editors and peers.…”
Section: Introductionmentioning
confidence: 99%